2021
DOI: 10.1186/s12936-021-03745-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artemether–lumefantrine for treatment of uncomplicated Plasmodium falciparum malaria in Ethiopia: a systematic review and meta-analysis

Abstract: Background Regular monitoring of anti-malarial drug efficacy is vital for establishing rational malaria treatment guidelines and ensuring adequate treatment outcomes. This study aimed to synthesize the available evidence on the efficacy of artemether–lumefantrine for the management of uncomplicated falciparum malaria in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…However, chloroquine (CQ) is still widely used and efficacious for cases of endemic vivax malaria 24 . Artemether-lumefantrine remains highly efficacious 25 , though detection of the candidate artemisinin resistance K13 622I mutation in northern Ethiopia 26,27 and high prevalence of residual submicroscopic parasitemia following ACT treatment in recent studies raises concern 12,25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, chloroquine (CQ) is still widely used and efficacious for cases of endemic vivax malaria 24 . Artemether-lumefantrine remains highly efficacious 25 , though detection of the candidate artemisinin resistance K13 622I mutation in northern Ethiopia 26,27 and high prevalence of residual submicroscopic parasitemia following ACT treatment in recent studies raises concern 12,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The PCR-corrected cure-rate of AL in our study is consistent with the PCR-corrected findings of previous studies conducted in Ethiopia [ 7 , 10 15 ] and with recent studies elsewhere in Africa [ 16 18 ] after 28 days of follow-up period. Moreover, a recent review has also showed the high cure rate of AL in Ethiopia [ 19 ]. These results strongly support that AL remains highly efficacious two decades after its implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the included studies was assessed by two authors (MK, WM) using the Jadad scale for reporting randomized controlled trials [ 24 ] and the strengthening of the reporting of observational studies in epidemiology (STROBE) [ 25 ] guidelines. For the Jadad scale, studies with scores of 0–3 were determined to be of poor quality, while studies with scores of 4–8 were determined to be of good to excellent quality (high quality), as described elsewhere [ 26 ]. For STROBE, the studies were categorized as either high quality (over 75% of the STROBE checklist) or low quality (under 75% of the STROBE checklist), as described elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%